The case for Proto-Mark : a study in the synoptic problem - Burkett, Delbert (Tubingen Mohr Siebeck, 2018)
Delbert Burkett addresses the Synoptic Problem, the question of what sources were used by the Synoptic Gospels (Matthew, Mark, and Luke). The most common explanation for the materials hared by Matthew and luke (the double tradition) is that Matthew and Luke both used a source now lost, called Q. If we adopt the Q hypothesis to account for the double tradition, then what theory best accounts for the material that Matthew and Luke share with Mark (the Markan material)? Three main theories have been proposed: Matthew and Luke used the Gospel of Mark as a source (the standard theory of Markan priority), Matthew and Luke used a revised version of Mark's gospel (the Deutero-Mark hypothesis), or all three evangelists used a source similar to, but earlier than, the Gospel of Mark (the Proto-Mark hypothesis). Delbert Burkett provides new data that calls into question the standard theory of Markan priority and the Deutero-Mark hypothesis. He offers the most comprehensive case to date for the Proto-Mark hypothesis, concluding that this theory best accounts for the Markan material.
Includes bibliographical references (pages 291-302) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; Synoptic problem